Serotonin and Memory - Alfredo Meneses (Frontiers Research Topics, 2016)
The study of 5-hydroxytryptamine (5-HT) systems has benefited from the identification, classification and cloning of multiple 5-HT receptors (5-HT1 to 5-HT7). Increasing evidence suggests that 5-HT pathways, reuptake site/transporter complex and 5-HT receptors represent a strategic distribution for learning and memory. A key question still remaining is whether 5-HT markers (e.g., receptors) are directly or indirectly contributing to the physiological and pharmacological basis of memory and its pathogenesis or, rather, if they represent protective or adaptable mechanisms. Certainly, Alzheimer´s disease (AD) is a very complex neuropsychiatric disorder, where memory becomes progressively dysfunctional resulting in amnesia and dementia, whereas forgetting is a physiological phenomenon occurring all the time as adaptive mechanism. As dysfunctional memory occurs in several neuropsychiatric disorders, including schizophrenia, stroke, post-traumatic stress disorder. Hence, the aim of this call is collect recent and important findings related to information about serotonin and memory or 5-HT and learning or 5-HT and memory or serotonin and learning.